Monetary Sanctions in Community Corrections: Law, Policy, and Their Alignment With Correctional Goals. (February 2021) - Ruhland, Ebony L.; Petkus, Amber A.; Link, Nathan W.; Hyatt, Jordan M.; Holmes, Bryan; Pate, Symone
The assessment and collection of monetary sanctions (fines, fees, and restitution) have become a common element of the U.S. criminal justice system, especially in community corrections. Although the application of monetary sanctions is often dictated by state-level legislation, court rules, and agency policy, little research has sought to organize and systematically examine a set of these policies to compare them across several community corrections contexts more broadly. As such, this study fills a gap in the literature by using thematic content analysis to examine legislative policies governing the use of monetary sanctions in six states from across the United States. Laws and policies regarding the assessment, waiver, and collection of monetary sanctions utilized by agencies of varying size and jurisdictional scope were considered to identify common themes. We conclude with a discussion of whether the policies and laws examined align with rehabilitative and punitive goals of community supervision and highlight emerging opportunities for research and policy reform.